The art of death stranding. (London : Titan Books, 2020)
"After the collapse of civilization, Sam Bridges must journey across a ravaged landscape crawling with otherworldly threats to save mankind from the brink of extinction. From legendary game creator Hideo Kojima comes an all-new, genre-defying experience for the PlayStation®4 system, nominated for the DICE Game of the Year Award. In the near future, mysterious explosions have rocked the planet, setting off a series of supernatural events known as the Death Stranding. With spectral creatures plaguing the landscape, and the planet on the verge of a mass extinction, it's up to Sam Bridges to journey across the ravaged continent and save mankind from impending annihilation. The Art of Death Stranding is packed with hundreds of pieces of concept art for the characters, equipment, locations and creatures featured in the game, as well as early and unused con cepts, including artwork by acclaimed artist Yoji Shinkawa." --amazon.com.
Keywords: Death Stranding (Game); Video game characters -- Design; Video games -- Design; Computer graphics; Video games -- Pictorial works